2022
DOI: 10.2460/javma.20.06.0358
|View full text |Cite
|
Sign up to set email alerts
|

Pathology in Practice

Abstract: In collaboration with the American College of Veterinary Pathologists

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…This reflects reported cases in humans 2 and most canine MIS. [10][11][12][13][14][15][16][17]19,24 Conversely to the recent canine CM study, 19 none of our cases showed aggressive histopathology features. This could be incidental due to the small number of biopsies reviewed or biased by our inclusion criteria.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…This reflects reported cases in humans 2 and most canine MIS. [10][11][12][13][14][15][16][17]19,24 Conversely to the recent canine CM study, 19 none of our cases showed aggressive histopathology features. This could be incidental due to the small number of biopsies reviewed or biased by our inclusion criteria.…”
Section: Discussionmentioning
confidence: 57%
“…19 The median age at diagnosis in the dogs reported here was 4-years-old, similar to previously described cases of canine CM. 10,[13][14][15][16]18,19,24 However, the age of lesion onset was 2-years-old (range 0.16-11.5) suggesting that the diagnosis of MIS may be delayed in certain cases. Notably, MIS lesions were only reported after 4 years of age in the four dogs with atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations